Analisis Portofolio Saham dengan Metode Capm dan Markowitz - Prabowo, Hartiwi (Bina Nusantara University, 2013)
Â LQ45 index is a row of 45 stocks with the largest commercial transactions in BEI. These stocks are also commonly referred to as blue-chip stocks. Stocks at LQ 45 index must meet the criteria and pass a predetermined key. The LQ 45 stocks are continuously being monitored and will be a reviewed for every 6 months (early February and August). Capital Asset Pricing Model (CAPM) is used to estimate the return of a securities, while minimizing the risk to the desired level of returns in stock investing can be done by way of diversification or invest the funds into more than one type of securities (forming portfolios). The purpose of this study was to determine the expected return, and choosing the best stocks to obtain the optimal portfolio composition and profitable to invest. This study uses secondary data, ie data LQ 45, stock prices, the level of available SBI Stock Exchange, BI, and websites. To analyze the data, the writer used method of CAPM and Markowitz Portfolio. The results showed the election of 5 stocks of the most profitable for investors, namely stock UNTR, SMCB, ASII, INDF and BBRI. For companies that issue stocks should interact more with the society and the capital markets to attract more investors.